Comparison Study of Fracture Resistance for Two Types of Indirect Aesthetic Resin Crowns Used in Restoring Pulp Treated Primary Molars (Journal of Hama University, 2020)
Recently, esthetic concerns has been increased dramatical for pediatric patient and their parents for the dental treatment, and because the lack of available esthetics choices in restoring pulp treated primary molars. This study was conducted to evaluate two type of esthetic primary molars crowns fabricated using two different methods, photopolymer Resin via 3-D dental printer, and using PMMA White Peaks blocks via Computer Aid Designed, Computer Aid Manufacturing CAD\CAM system in fracture resistance force and type of fracture.Twenty second lower primary molar prepared for crowning using digital design via “Exocade software ” were divided in two experimental groups, 10 molars for each group as following, Group A: 3D dental printer to fabricate crowns using GC photopolymer resin, Group B: CAD\CAM crowns using polymethylmethacrylate (PMMA) blocks, the crowns were cemented to the prepared teeth using GC resin cement and allowed to set for 24 hours. The crowned teeth were tested using Testometric machine , the fracture resistance force were recorded and fracture type were evaluated . No statistically significant differences are noted when using independent Sample T Test in terms of fracture resistance force FRF experimental test between Group A\B (P= 0.146), No statistical differences were noted In Failure type when comparing the two groups in qi-square test (P= 0.080). The two tested esthetic crowns exceeded the mean maximum bite force of children in the mixed dentition thus, they are prone to be able to be used clinically with no statistical differences between the 3D- Printed crowns and CAD\CAM fabricated crowns in FRF and failure type.